Feeding desensitizes A1 adenosine receptors in adipose through FOXO1-mediated transcriptional regulation - Mitchell E. Granade; Stefan R. Hargett; Daniel S. Lank; Michael C. Lemke; Melissa A. Luse; Brant E. Isakson; Irina M. Bochkis; Joel Linden; Thurl E. Harris (Elsevier, 2022)
Objective: Adipose tissue is a critical regulator of energy balance that must rapidly shift its metabolism between fasting and feeding to maintain homeostasis. Adenosine has been characterized as an important regulator of adipocyte metabolism primarily through its actions on A1 adenosine receptors (A1R). We sought to understand the role A1R plays specifically in adipocytes during fasting and feeding to regulate glucose and lipid metabolism. Methods: We used Adora1 floxed mice with an inducible, adiponectin-Cre to generate FAdora1−/− mice, where F designates a fat-specific deletion of A1R. We used these FAdora1−/− mice along with specific agonists and antagonists of A1R to investigate changes in adenosine signaling within adipocytes between the fasted and fed state. Results: We found that the adipose tissue response to adenosine is not static, but changes dynamically according to nutrient conditions through the insulin-Akt-FOXO1 axis. We show that under fasted conditions, FAdora1−/− mice had impairments in the suppression of lipolysis by insulin on normal chow and impaired glucose tolerance on high-fat diet. FAdora1−/− mice also exhibited a higher lipolytic response to isoproterenol than WT controls when fasted, however this difference was lost after a 4-hour refeeding period. We demonstrate that FOXO1 binds to the A1R promoter, and refeeding leads to a rapid downregulation of A1R transcript and desensitization of adipocytes to A1R agonism. Obesity also desensitizes adipocyte A1R, and this is accompanied by a disruption of cyclical changes in A1R transcription between fasting and refeeding. Conclusions: We propose that FOXO1 drives high A1R expression under fasted conditions to limit excess lipolysis during stress and augment insulin action upon feeding. Subsequent downregulation of A1R under fed conditions leads to desensitization of these receptors in adipose tissue. This regulation of A1R may facilitate reentrance into the catabolic state upon fasting.